Optical antistatic polyester film and preparation method thereof

By using aqueous resin and composite dispersion of carbon nanotubes and graphene as antistatic coating raw materials, combined with three-layer coextrusion layer and online coating technology, the problems of easy migration and humidity dependence of antistatic agents are solved, and a high-performance optical antistatic polyester film is achieved.

CN120329592APending Publication Date: 2025-07-18ZHANGJIAGANG KANGDE XIN OPTRONICS MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510252393.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The antistatic agents of the existing antistatic polyester films are easy to migrate and their performance depends on the environmental humidity, have high requirements for use, and are prone to crystal points and fog points when applied in the optical field.

Method used

The composite dispersion of aqueous resin and carbon nanotubes and graphene is used as the raw material for anti-static coating, and the anti-static polyester film is formed through a three-layer coextruded layer structure and online coating technology, combined with longitudinal and transverse stretching treatment.

Benefits of technology

It achieves antistatic properties without being affected by environmental humidity, is low in cost, is environmentally friendly and has good anti-adhesion, smoothness and high light transmittance, and is suitable for optical-grade films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120329592A_ABST
    Figure CN120329592A_ABST
Patent Text Reader

Abstract

The invention relates to an optical antistatic polyester film and a preparation method thereof. The optical antistatic polyester film comprises a polyester layer and an antistatic coating, the antistatic coating is arranged on the surface of at least one side of the polyester layer, and raw materials for forming the antistatic coating comprise water-based resin and composite dispersion liquid of carbon nanotubes and graphene. According to the optical antistatic polyester film, a three-layer co-extrusion mode is adopted, the polyester preparation layer is coated with the antistatic coating on line after longitudinal stretching and before transverse stretching, and the optical antistatic polyester film is formed. According to the optical antistatic polyester film, the problems that an existing antistatic agent is prone to migration, the antistatic performance depends on environment humidity, and the requirement for the use environment is high are solved, and the optical performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of optical thin films, and particularly relates to an optical antistatic polyester film and a preparation method thereof. Background Art

[0002] Biaxially oriented polyester film (BOPET) has shown extensive application potential in multiple fields due to its high strength, good rigidity, high transparency and gloss, as well as its odorless, tasteless, colorless, non-toxic and outstanding toughness. From traditional packaging, printing, window films, solar backsheets to high-end optical films such as antireflection films, prism films, diffusion films and hardening films, BOPET film has become an indispensable material.

[0003] In the prior art, the antistatic performance of the film is generally solved by adding an antistatic agent to the polyester or coating the antistatic agent on the surface. For the internally added antistatic polyester film, the antistatic agent needs to be blended with polyester particles containing micron-sized SiO2 to form a masterbatch, and then extruded and formed on the surface of the polyester film after high-temperature melting at 280°C together with the pure polyester masterbatch. Since the antistatic component needs to withstand high temperatures and realizes the antistatic performance by migrating to the surface of the polyester film, the types that can be selected are few and the antistatic performance is poor.

[0004] Currently, there are mainly two methods for coating antistatic films. One is offline coating, and the other is online coating. The antistatic coating glue required for offline coating is all organic solvents, which causes large pollution, thick coating, and the coating liquid needs to be coated on BOPET, adding an extra process and increasing the cost. In online coating, the antistatic coating liquid is all water-based coating liquid, and the currently used antistatic agents are mostly surfactant-based and conductive polymer-based. The antistatic performance of surfactant-based antistatic agents depends on the environmental humidity. In a dry environment, the antistatic performance disappears, and the requirements for the use environment are relatively high. The antistatic performance can only be reflected when the humidity is higher than 40% at 25°C.

[0005] For offline or online coating of polythiophene conductive polymer (PEDOT), in this method, the conductive performance of the coating is not affected by the environmental temperature and humidity, but it cannot be exposed to sunlight for a long time, and the substrate cannot be corona treated, the surface dyne value is low, and the recoatability of the downstream is limited.

[0006] Currently, in the existing antistatic films, micron-sized SiO2 slip particles are added to the polyester to solve the anti-adhesion and slip effects of the film. However, due to the relatively large particle size of micron-sized SiO2 and the large addition amount, it is easy to form crystal points and fog points on the film, and the film cannot be applied to the optical grade field. Summary of the Invention

[0007] The main object of the present invention is to provide an optically antistatic polyester film and a preparation method thereof, so as to solve the problems that the existing antistatic agents are prone to migration, and the antistatic performance depends on environmental humidity, with high requirements for the use environment.

[0008] To achieve the above object, according to one aspect of the present invention, there is provided an optically antistatic polyester film, comprising a polyester layer and an antistatic coating, wherein the antistatic coating is disposed on at least one surface of the polyester layer, and the raw materials for forming the antistatic coating include an aqueous resin and a composite dispersion liquid of carbon nanotubes and graphene.

[0009] Further, the aqueous resin is one or more of aqueous polyurethane, aqueous acrylate or aqueous polyester.

[0010] Further, the mass ratio of the total mass of carbon nanotubes and graphene in the composite dispersion liquid of carbon nanotubes and graphene to the mass of the aqueous resin is 1:9 to 1:1.

[0011] Further, the mass ratio of carbon nanotubes to graphene is 3:1 to 5:1.

[0012] Further, the carbon nanotubes are single-walled carbon nanotubes, the diameter of the carbon nanotubes is 1 to 2 nm, and the length is 1 to 2 μm; the graphene is 5 to 30 layers of multi-layer graphene.

[0013] Further, the composite dispersion liquid of carbon nanotubes and graphene further contains a sulfonic acid resin and first nanoparticles, and the average particle size of the first nanoparticles is 50 to 100 nm.

[0014] Further, the antistatic coating further contains sub-micron particles, and the particle size of the sub-micron particles is 0.08 to 0.3 μm.

[0015] Further, the polyester layer is an ABA three-layer co-extruded layer, wherein the A layer includes a polyester masterbatch containing second nanoparticles and polyester white chips, and the mass ratio of the polyester masterbatch containing second nanoparticles to the polyester white chips is 0.05 to 0.15:1; the B layer is a polyester white chip layer.

[0016] Further, the average particle size of the second nanoparticles is 10 to 50 nm.

[0017] According to another aspect of the present invention, there is provided a preparation method of an optically antistatic polyester film, comprising the following steps:

[0018] S1, preparing an antistatic coating liquid by using raw materials including an aqueous resin and a composite dispersion liquid of carbon nanotubes and graphene,

[0019] S2, coating the antistatic coating liquid on one surface of a polyester preparatory layer,

[0020] S3. Cure the antistatic coating liquid to form an antistatic coating.

[0021] Further, before step S2, there is also a step of preparing the polyester preliminary layer, including: feeding a polyester mixed masterbatch containing second nanoparticles and polyester white chips into a secondary extruder, feeding the polyester white chips into a primary extruder, co-extruding three layers, and performing longitudinal stretching treatment to form a polyester preliminary layer;

[0022] After step S2, perform transverse stretching treatment on the polyester preliminary layer coated with the antistatic coating liquid.

[0023] Compared with the prior art, the present application has the following beneficial effects:

[0024] The optical antistatic polyester film of the present invention includes a polyester layer and an antistatic coating, and the raw materials for forming the antistatic coating include an aqueous resin and a composite dispersion liquid of carbon nanotubes and graphene. The antistatic performance has no requirement for environmental humidity. Using an on-line coating method, it can be stretched on-line. After being stretched 4 times, the antistatic performance is still good. It has low cost, no organic solvents, is more environmentally friendly, and has better environmental aging performance. It can be corona processed to increase the dyne value of the substrate and thus improve the recoatability.

[0025] Moreover, the present invention only adds a small amount of nano-scale particles as crystal nuclei to the polyester layer to improve the surface crystallinity of the film, thereby increasing the surface hardness and preventing scratches. At the same time, sub-micron-scale particles are added to the antistatic coating to make the film have anti-adhesion and smoothness properties. Due to the thin coating, the addition amount of sub-micron-scale particles is small, and nano-scale particles are used in the polyester layer. While solving the smoothness, the polyester film has low haze, high light transmittance, and excellent surface cleanliness and slitting performance. Description of the Drawings

[0026] Figure 1 It is a schematic structural diagram of the optical antistatic polyester film in an embodiment of the present application.

[0027] Figure 2 It is a schematic structural diagram of the optical antistatic polyester film in another embodiment of the present application.

[0028] Figure 3 It is a schematic structural diagram of the polyester layer of the present application.

[0029] Description of the reference numerals: 10. Polyester layer; 20. Antistatic coating, A. Surface layer, B. Core layer. Detailed Embodiments

[0030] To make the above objects, features, and advantages of the present application more apparent and understandable, the following provides a detailed description of the specific embodiments of the present application in conjunction with the accompanying drawings. It can be understood that the specific embodiments described herein are only for explaining the present application and not for limiting the present application. Additionally, it should be noted that for ease of description, only the parts related to the present application rather than all the structures are shown in the drawings. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the scope of protection of the present application.

[0031] The terms "comprising" and "having" in this application and any variations thereof are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but optionally further includes steps or units not listed, or optionally further includes other steps or units inherent to these processes, methods, products, or devices.

[0032] Referring to "embodiments" herein means that specific features, structures, or characteristics described in connection with the embodiments can be included in at least one embodiment of the present application. The phrase appears in various places in the specification and does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art explicitly and implicitly understand that the embodiments described herein can be combined with other embodiments.

[0033] As introduced in the background art, currently, internal addition type or coating type antistatic agents are environment-dependent, with their antistatic performance disappearing in a dry environment and being prone to migration. In view of the above problems, the present invention proposes an optical antistatic polyester film, as Figure 1 shown, comprising a polyester layer 10 and an antistatic coating 20. The antistatic coating 20 is disposed on at least one surface of the polyester layer 10, and the raw materials for forming the antistatic coating 20 include an aqueous resin and a composite dispersion of carbon nanotubes and graphene.

[0034] The above antistatic coating contains an aqueous resin and a composite dispersion of carbon nanotubes and graphene. The composite dispersion of carbon nanotubes and graphene gives the film surface good antistatic performance, and the antistatic performance has no requirement for environmental humidity. At the same time, it can be stretched online, and the antistatic performance remains good after being stretched 4 times. It has a low cost, no organic solvents, is more environmentally friendly, and has better environmental aging performance. It can be corona processed to increase the dyne value of the substrate and thus improve the recoatability.

[0035] In the present invention, the antistatic coating 20 can be disposed on one surface of the polyester layer 10, as Figure 1 shown, or can be disposed on both surfaces of the polyester layer 10, as Figure 2 shown.

[0036] The aqueous resin of the present invention can be one or more of aqueous polyurethane, aqueous acrylate or aqueous polyester.

[0037] In the composite dispersion of carbon nanotubes and graphene, the mass ratio of the total mass of carbon nanotubes and graphene to the mass of the aqueous resin is 1:9 to 1:1. With the above ratio, the composite dispersion of carbon nanotubes and graphene can be better dispersed uniformly with the aqueous resin, and has excellent electrical conductivity and excellent adhesion between the antistatic coating and the polyester layer. Preferably, the mass ratio of the total mass of carbon nanotubes and graphene to the aqueous resin is 1:2.

[0038] The mass ratio of the above-mentioned carbon nanotubes to graphene is 3:1 to 5:1. With the above ratio, carbon nanotubes and graphene can be dispersed uniformly and have good antistatic performance. More preferably, the mass ratio of nanotubes to graphene is 4:1.

[0039] The above-mentioned carbon nanotubes are single-walled carbon nanotubes. Compared with multi-walled carbon nanotubes, the single-walled carbon nanotubes of the present invention have better electrical conductivity, lighter color and do not affect the optical properties of the coating. The diameter of the carbon nanotubes is 1 to 2 nm and the length is 1 to 2 μm.

[0040] The above-mentioned graphene is multi-layer graphene with 5 to 30 layers. The multi-layer graphene has the advantages of excellent electrical conductivity, low cost, light color and good transparency.

[0041] In a preferred embodiment, the composite dispersion of carbon nanotubes and graphene further contains a sulfonic acid resin and a first nanoparticle. Since carbon nanotubes and graphene are inorganic substances, it is difficult to homogeneously disperse them in water. During the ball milling dispersion process, a sulfonic acid resin and a first nanoparticle are added as grinding and dispersing aids, so that carbon nanotubes and graphene can form a stable aqueous dispersion uniformly and can be well blended and dispersed with the aqueous resin. The above-mentioned first nanoparticle can be silicon dioxide, zirconium oxide, zirconium oxide, etc., and preferably nano-SiO2. The average particle size of the above-mentioned first nanoparticle is 50 to 100 nm.

[0042] In a preferred embodiment, the above-mentioned antistatic coating further contains submicron particles, so that the film has anti-adhesion and smoothness properties. The submicron particles can be selected from common organic or inorganic particles, such as silicon dioxide, zirconium oxide, zirconium oxide, PMMA, PS, etc., and preferably SiO2 particles. The particle size of the above-mentioned submicron particles is 0.08 to 0.3 μm.

[0043] In the present invention, the raw materials for forming the antistatic coating further include isopropyl alcohol, wetting agent, curing agent, pH regulator, deionized water, etc. The above-mentioned wetting agent may include one or more of alkynediol, fluorine-based and methylene sulfoxide; the above-mentioned curing agent may include any one or more of melamine, oxazoline and isocyanate; the above-mentioned pH regulator is an amine compound, such as at least one of 2-amino-2-methyl-1-propanol, ammonia water, diethanolamine, and triethanolamine..

[0044] In the present invention, as Figure 3 shown, the polyester layer 10 is an ABA three-layer co-extruded layer. The A layer is the surface layer, including a polyester masterbatch containing second nanoparticles and polyester white chips, and the mass ratio of the polyester masterbatch containing second nanoparticles to the polyester white chips is 0.05 to 0.15:1. The B layer is the core layer, containing 100% polyester white chips.

[0045] In a preferred embodiment, the above-mentioned second nanoparticles may be inorganic or organic particles, preferably SiO2 particles. The average particle size of the second nanoparticles is 10 to 50 nm.

[0046] According to another aspect of the present invention, a method for preparing an optically antistatic polyester film is provided.

[0047] The masterbatch containing nano-SiO2 and ordinary polyester white chips are mixed evenly according to the ratio and then added to the auxiliary extruder. They are respectively fed into the main extruder and the auxiliary extruder (two) for melting. After passing through the metering pump, melt pipe, coarse filter, fine filter, distributor, and co-extrusion die head, three-layer melt is extruded. The melt passes through the electrostatic adsorption device and forms a thick sheet on the chill roll.

[0048] The thick sheet coming out of the chill roll is preheated by a preheating roll group at 60 to 130 °C for 5 to 15 seconds, and then enters the far-infrared region at 130 to 150 °C for heating. The heating time is 1.5 to 5 seconds. Under the action of the stretching roll under this condition, the longitudinal stretching of the thick sheet is completed, and the stretching ratio is 2.8 to 3.5:1. Subsequently, the film is relaxed and cooled at 20 to 30 °C to form a polyester pre-layer.

[0049] The longitudinally stretched film, after cooling and relaxation, enters the coater. By means of D-bar scraping coating, the previously prepared antistatic coating liquid is coated on one side surface of the polyester pre-layer. According to the size of the coating amount, the size of the hanging rod is adjusted to make the surface coating liquid evenly coated on the film surface.

[0050] After coating the film, both sides are clamped by chain clamps and enter the transverse stretching oven, where they are preheated at a temperature of 70 - 110°C for 3 - 8 seconds, then transversely stretched at a temperature of 90 - 130°C with a transverse stretching ratio of 3.3 - 4.3:1. Subsequently, heat setting is carried out at a temperature of 180 - 240°C, and the heat setting time is controlled within 5 - 10 seconds. The coating liquid on the film surface solidifies during this process. After heat setting, the film is immediately subjected to relaxation cooling at a temperature of 45 - 160°C. The film after extrusion, longitudinal stretching, surface coating, transverse stretching, and heat setting is wound under the traction of the traction roller (the non-coated surface is corona treated before winding). Finally, slitting is carried out as required.

[0052] To more clearly elaborate on the technical solution of this application, it is described below in conjunction with specific implementation cases.

[0053] Example 1

[0054] An optical antistatic polyester film is composed of a polyester layer and an antistatic coating, and the antistatic coating is provided on one surface of the polyester layer. The polyester layer is a coextruded film with a three-layer ABA structure, where A is the surface layer and B is the core layer. The surface layer material is a polyester masterbatch mixed with nanoscale SiO2 particles (average particle size 10 - 50nm) with a mass ratio of 0.05:1 and polyester white chips; the core layer is a 100% polyester white chip layer.

[0055] The components and weight percentages of the coating liquid for the antistatic coating are as follows: 2% water-based resin, 20% composite dispersion liquid of carbon nanotubes and graphene (mass ratio of carbon nanotubes to graphene is 4:1), 0.2% SiO2 dispersion liquid (particle size is 0.08 - 0.3μm), 0.03% wetting agent, 0.01% pH regulator, and 77.76% deionized water. After stirring evenly, the prepared coating liquid is coated on one side of the longitudinally stretched polyester film, then enters the transverse stretching area for 3.5 times stretching, and finally heat set at 220°C for 8 seconds to obtain an optical polyester film with a film thickness of 125μm.

[0056] Example 2

[0057] An optical antistatic polyester film is composed of a polyester layer and an antistatic coating, and the antistatic coating is provided on one surface of the polyester layer. The polyester layer is a coextruded film with a three-layer ABA structure, where A is the surface layer and B is the core layer. The surface layer material is a polyester masterbatch mixed with nanoscale SiO2 particles (average diameter 10 - 50nm) with a mass ratio of 0.08:1 and polyester white chips; the core layer is a 100% polyester white chip layer.

[0058] The components and weight percentages of the coating liquid for the antistatic coating are as follows: 3% waterborne resin, 20% composite dispersion of carbon nanotubes and graphene (the mass ratio of carbon nanotubes to graphene is 4:1), 0.1% SiO2 dispersion (particle size is 0.08 - 0.3 μm), 0.03% wetting agent, 0.01% pH regulator, and 76.86% deionized water. After stirring evenly, the prepared coating liquid is coated on one side of the longitudinally stretched sheet of the polyester film, then enters the transverse stretching area for 3.5 times stretching, and finally undergoes heat setting at 220 °C for 8 seconds to obtain an optical polyester film with a film thickness of 125 μm.

[0059] Example 3

[0060] An optical antistatic polyester film is composed of a polyester layer and an antistatic coating, and the antistatic coating is provided on one side surface of the polyester layer. The polyester layer is a three-layer coextruded film with an ABA structure, where A is the surface layer and B is the core layer. The surface layer material is a polyester masterbatch mixed with nanoscale SiO2 particles (average diameter 10 - 50 nm) with a mass ratio of 0.1:1 and polyester white chips; the core layer is a 100% polyester white chip layer.

[0061] The components and weight percentages of the coating liquid for the antistatic coating are as follows: 3% waterborne resin, 20% composite dispersion of carbon nanotubes and graphene (the mass ratio of carbon nanotubes to graphene is 4:1), 0.05% SiO2 dispersion (particle size is 0.08 - 0.3 μm), 0.03% wetting agent, 0.01% pH regulator, and 76.91% deionized water. After stirring evenly, the prepared coating liquid is coated on one side of the longitudinally stretched sheet of the polyester film, then enters the transverse stretching area for 3.5 times stretching, and finally undergoes heat setting at 220 °C for 8 seconds to obtain an optical polyester film with a film thickness of 125 μm.

[0062] Example 4

[0063] An optical antistatic polyester film is composed of a polyester layer and an antistatic coating, and the antistatic coating is provided on one side surface of the polyester layer. The polyester layer is a three-layer coextruded film with an ABA structure, where A is the surface layer and B is the core layer. The surface layer material is a polyester masterbatch mixed with nanoscale SiO2 particles (average diameter 10 - 50 nm) with a mass ratio of 0.12:1 and polyester white chips; the core layer is a 100% polyester white chip layer.

[0064] The components and weight percentages of the coating liquid for the antistatic coating are as follows: 3% water-based resin, 15% composite dispersion of carbon nanotubes and graphene (the mass ratio of carbon nanotubes to graphene is 3:1), 0.05% SiO2 dispersion (particle size is 0.08 - 0.3 μm), 0.03% wetting agent, 0.01% pH regulator, and 81.91% deionized water. After stirring evenly, the prepared coating liquid is coated on one side of the longitudinally stretched sheet of the polyester film, then enters the transverse stretching area for 3.5 times stretching, and finally undergoes heat setting at 220 °C for 8 seconds to obtain an optical polyester film with a film thickness of 125 μm.

[0065] Example 5

[0066] An optical antistatic polyester film is composed of a polyester layer and an antistatic coating, and the antistatic coating is provided on one side surface of the polyester layer. The polyester layer is a coextruded film with a three-layer ABA structure, where A is the surface layer and B is the core layer. The surface layer material is a polyester masterbatch mixed with nanoscale SiO2 particles (average diameter 10 - 50 nm) with a mass ratio of 0.15:1 and polyester white chips; the core layer is a 100% polyester white chip layer.

[0067] The components and weight percentages of the coating liquid for the antistatic coating are as follows: 3% water-based resin, 25% composite dispersion of carbon nanotubes and graphene (the mass ratio of carbon nanotubes to graphene is 5:1), 0.05% SiO2 dispersion (particle size is 0.08 - 0.3 μm), 0.03% wetting agent, 0.01% pH regulator, and 71.91% deionized water. After stirring evenly, the prepared coating liquid is coated on one side of the longitudinally stretched sheet of the polyester film, then enters the transverse stretching area for 3.5 times stretching, and finally undergoes heat setting at 220 °C for 8 seconds to obtain an optical polyester film with a film thickness of 125 μm.

[0068] Comparative Example 1

[0069] Except that no nanoscale SiO2 particles are added to the antistatic coating, the others are basically the same as in Example 3, and finally an optical polyester film with a thickness of 125 μm is obtained.

[0070] Comparative Example 2

[0071] The addition amount of nanoscale SiO2 particles in the antistatic coating is 0.5%, and except for this, the others are basically the same as in Example 3, and finally an optical polyester film with a thickness of 125 μm is obtained.

[0072] Comparative Example 3

[0073] No blend liquid of carbon nanotubes and graphene is added to the polyester film, and a 5% ordinary surfactant antistatic coating liquid is used. Except for this, the others are basically the same as in Example 3, and finally an optical polyester film with a thickness of 125 μm is obtained.

[0074] The methods for various physical property tests of this application are as follows:

[0075] (1) Surface resistance test:

[0076] Under the specified temperature and humidity environment, use the WA-400 handheld surface resistance meter produced by TAIYO ELECTRIC IND.CO.,LTD to test the antistatic layer resistance

[0077] (2) Transmittance and haze test:

[0078] Adopt the AT-4725 transmission haze meter of BYK Chemie GmbH in Germany, and the reference standard is ASTM D 1003.

[0079] (3) Slip property test:

[0080] The coating effect on the film surface is rated according to the following method:

[0081] ●: Good slip property, can be slit, not sticky; ○: Poor slip property, sticky. Among them, ● is qualified, and ○ and △ are unqualified.

[0082] (4) Dyn value test of corona surface:

[0083] Use a dyn pen to test the dyn value.

[0084] Table 1 Data table of various physical property tests of examples and comparative examples

[0085]

[0086] As can be seen from the above table, in Comparative Example 1, nano-SiO2 particles were not added to the antistatic coating, and the polyester film had poor slip property and was easy to stick. In Comparative Example 2, the addition amount of nano-SiO2 particles in the antistatic coating was 0.5%, the addition amount was large, and the clarity of the polyester film was poor. In Comparative Example 3, the composite dispersion liquid of carbon nanotubes and graphene was not added to the polyester film, and a 5% ordinary surfactant antistatic coating solution was used, and the antistatic performance was greatly affected by the environmental temperature and humidity.

[0087] The optical antistatic polyester film of the present invention includes a polyester layer and an antistatic coating, and the raw materials for forming the antistatic coating include an aqueous resin and a composite dispersion liquid of carbon nanotubes and graphene. The antistatic performance has no requirement for environmental humidity. Adopt the online coating method, can be stretched online, and the antistatic performance is still good after being stretched 4 times. It has low cost, no organic solvents, is more environmentally friendly, and has better environmental aging performance. It can be corona processed to increase the dyn value of the substrate and thus improve the recoatability.

[0088] Moreover, only a small amount of nano-sized particles are added to the polyester layer as crystal nuclei in the present invention to increase the surface crystallinity of the film, thereby increasing the surface hardness and preventing scratches. At the same time, sub-micron-sized particles are added to the antistatic coating to endow the film with anti-adhesion and smoothness properties. Due to the thin coating, the small addition amount of sub-micron-sized particles, and the use of nano-sized particles in the polyester layer, the polyester film has low haze, high light transmittance, clean surface, and excellent production and slitting performance while solving the smoothness problem.

[0089] The above is only a specific embodiment of the present application, and any improvement made on the premise of the concept of the present application is regarded as the protection scope of the present application.

Claims

1. An optical antistatic polyester film, characterized in that, It includes a polyester layer and an antistatic coating. The antistatic coating is disposed on at least one surface of the polyester layer, and the raw materials for forming the antistatic coating include an aqueous resin and a composite dispersion of carbon nanotubes and graphene.

2. The optical antistatic polyester film according to claim 1, wherein In the composite dispersion of carbon nanotubes and graphene, the total mass ratio of carbon nanotubes and graphene to the mass of the aqueous resin is 1:9 to 1:

1.

3. The optical antistatic polyester film according to claim 1 or 2, characterized in that, The mass ratio of the carbon nanotubes to the graphene is 3:1 to 5:

1.

4. The optical antistatic polyester film according to claim 1, wherein The carbon nanotubes are single-walled carbon nanotubes with a diameter of 1 to 2 nm and a length of 1 to 2 μm; the graphene is multi-layer graphene with 5 to 30 layers.

5. The optical antistatic polyester film according to claim 1, wherein The composite dispersion of carbon nanotubes and graphene further contains a sulfonic acid resin and first nanoparticles. Preferably, the average particle size of the first nanoparticles is 50 to 100 nm.

6. The optical antistatic polyester film according to claim 1, wherein The antistatic coating further contains submicron particles with a particle size of 0.08 to 0.3 μm.

7. The optical antistatic polyester film according to claim 1, wherein, The polyester layer is an ABA three-layer co-extruded layer. The A layer includes a polyester masterbatch containing second nanoparticles and polyester white chips. The mass ratio of the polyester masterbatch containing second nanoparticles to the polyester white chips is 0.05 to 0.15:1; the B layer is a polyester white chip layer.

8. The optical antistatic polyester film according to claim 7, wherein The average particle size of the second nanoparticles is 10 to 50 nm.

9. A preparation method of an optical antistatic polyester film, characterized in that, It includes the following steps: S1, preparing an antistatic coating solution using raw materials including an aqueous resin and a composite dispersion of carbon nanotubes and graphene, S2, coating the antistatic coating solution on one surface of a polyester pre-layer, S3, curing the antistatic coating solution to form an antistatic coating.

10. The method for preparing an optically antistatic polyester film according to claim 9, wherein, Before step S2, it further includes the step of preparing the polyester pre-layer, including: feeding a polyester masterbatch containing second nanoparticles and polyester white chips into an auxiliary extruder, feeding the polyester white chips into a main extruder, performing three-layer co-extrusion, and performing longitudinal stretching treatment to form a polyester pre-layer; After step S2, performing transverse stretching treatment on the polyester pre-layer coated with the antistatic coating solution.